Pseudoscopas carbonelli n. sp. (Orthoptera: Acrididae: Melanoplinae) from southern Brazil, including chromosome complement - Costa, Maria Kátia Matiotti Da; Acosta, Riuler Corrêa; Timm, Vítor Falchi; Demari, Christian Peter; Carvalho, Gervásio Silva; Zefa, Edison (Zootaxa, 2021)
New species of Pseudoscopas (Orthoptera, Acrididae, Melanoplinae). Pseudoscopas carbonelli n. sp. from São Francisco de Paula, State of Rio Grande do Sul, Brazil is described, and a key to the species of Pseudoscopas Hebard, 1931 is added. Morphological descriptions are provided together with illustrations emphasizing the most significant diagnostic features of external morphology and male genitalia. Pseudoscopas carbonelli n. sp. differs from the other species known by epiproct with six protuberances in the median region, and extremities of the apical region of the epiproct sclerotized, as well as the lophi with sclerotization. Chromosome analyses were performed using standard staining procedures, showing diploid number of 2n = 23, X0♂/24, XX♀, and the karyotype made up of exclusively acrocentric chromosomes, including a medium-size megameric chromosome. Information is given about type specimens, material examined and geographic distribution.